Hubungan Dukungan Keluarga dengan Kepatuhan Diet Pasien Diabetes Mellitus Tipe-II - Oktavera, Ariska; Putri, Lydia Mardison; Dewi, Ratna (REAL in Nursing Journal, 2021)
Background: Diabetic diet management can be done by the family because the family is the main assistance in carrying out dietary compliance. Purpose:The purpose of this study was to determine the correlation between family support toward  Diet Compliance Of Diabetes Mellitus Type II Patients in Semerap Community Health Center, Kerinci Distict, 2020. Methods:The Type of this research was quantitative research. With Cross Sectional approach. Purposive sampling Had been  used to select the samples.. Then, it was analyzed by Statistical test with Chi-square. Result:The results showed that from 50 respondents, 16 (76.2%) respondents did not obedient and received less family support related to the diet. 21(72.4%) respondents obeyed a good diet and received good family support toward in their diet. Conclusion: The results of statistical thes showed that the p-value was 0.002 . It means that there was a significant  realationship between family suppport and dietary adherence to type II Diabetes Mellitus Patien. Last, it is Suggested to diabetes mellitus patients type II to set the right amount of diet in the implementation of dietary compliance. Furthermore, families are expected to be able to better understand and participante in providing family support (emotional support) to patien suffering from diabetes mellitus.Keywords: Family Support, Diet Compliance, Diabetes Mellitus tipe- II